Literature Review : Komunikasi Efektif Dalam Pelaksanaan Interprofessional Kolaborasi Di Rumah Sakit - Noor Lita Sari; Anisa Noviyanti (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
Interprofessional collaboration (IPC) is a collaboration between health professionals with different educational backgrounds to form a collaborative team to improve the quality of effective health services. The purpose of this research is to find out the types of professions involved in interprofessional collaboration, to know the components of effective communication in interprofessional collaboration, to know the components of collaboration in the application of interprofessional collaboration, to know the inhibiting factors in interprofessional collaboration. The method used is Literature Review design. The results showed that the components of collaboration in the application of interprofessional collaboration are cooperation, partnership, coordination, and decision making. The inhibiting factors for interprofessional collaboration communication are attitudes and behavior, there are still officers who are lazy, forgetful, tired, different opinions, and in a hurry which causes the CPPT documentation to be ineffective. So it is recommended for the leader to motivate his subordinates by giving sanctions and punishments.